(untitled) (Revista NUPEART, 2021)
This paper presents the results of a Pedagogical Proposal of literary and theatrical appropriation, based on the novel Dom Casmurro by Machado de Assis, in the context of the subject of Arts at Colégio Estadual São Cristóvão, in União da Vitória, Paraná, linked to the Mestrado Profissional in Arts - UDESC. Following the guidelines of the legal frameworks of the BNCC and the Education Guidelinesof the state Paraná. We investigated the possibilities of fostering repertoire for creative theatrical processes at school through literature, shared reading, collaborative writing and theatrical games. The methodology applied to the practice was action research with participatory research procedures and bibliographic research. The main concepts under discussion are shared reading (VIDOR, 2016), literary reception (ZUMTHOR, 2000), the pleasure and enjoyment of the text (BARTHES, 2015), appropriation in the context of literature and theater (MARTINS, 2004), individual and collaborative writing (NICOLETE, 2002), scenic composition (PUPO, 2005 and MARTINS, 2004). The appropriation process resulted in three scenes that were built together and presented as a result to the school community.